Validation of an RPHPTLC-Densitometric Method Using Silica Gel 60 RP18WF254 for Simultaneous Determination of Nicotinamide in Selected Pharmaceutical Formulations - Małgorzata Dołowy; Alina Pyka (Journal of Analytical Methods in Chemistry)
This research study describes the applicability of silica gel 60 RPW18F254 plates for the development and validation of new, simple, economic, accurate, and precise RPHPTLC-densitometric method suitable for the quantification of nicotinamide (as Vitamin PP) in three marketed preparations. The mobile phase used was methanol-water in volume composition 3 : 7. Detection wavelength was 200 nm. The proposed method was validated according to ICH guidelines and also based on Ferenczi-Fodor and Konieczka reports. Results were found to be linear over a range of 1.00 to 2.00 μg/spot. Limit of detection (LOD) and limit of quantification (LOQ) were 0.15 μg/spot and 0.45 μg/spot, respectively. The percent content of nicotinamide in the investigated preparations was found to be 99.2% (Product 1), 99.3% (Product 2), and 99.4% (Product 3). Developed method is accurate and precise (CV<3%) and may be successfully applied for the quality control of pharmaceutical formulations containing nicotinamide in the presence of its derivatives, such as N,N-diethylnicotinamide, N-methylnicotinamide, and nicotinic acid.